Potensi Trichoderma harzianum sebagai Biofungisida pada Tanaman Tomat ( Trichoderma harzianum Potency as a Biofungicide on Tomato Plant ) - Herlina, Lina (Biosaintifika: Journal of Biology & Biology Education, 2009)
Fusarium disease of tomato plant is caused by Fusarium oxysporum. For gaining high quality and stable tomato production but physically construction, natural management of environment balancing, consistency, and stability is a must. A kind effort that should be tried is using natural agent, Trichoderma. This research aims to know the effect of Trichoderma implementation towards Fusarium oxysporum growth, and Tomato fruit production and vitamin content. There are two steps of this research. The first is seeing Trichoderma perform towards Fusarium oxysporum growth in a variation of incubation periode (7, 14. 21 and 28 days). The second, is giving Trichoderma agent on the tomato planting in some dozez (g), such as 0,10,20,30,40 and 50. The parameter are Fusarium oxysporum growth limits area, fruit weight per plant, and fruit vitamin C content. The research shows that Trichoderma giving are effecting Fusarium oxysporum growth, tomato fruit weight and fruit vitamin C content in a significance way. The highest level of vitamin C content (84,78 mg/matterial) and fruit weight (550 g) is gained on Trichoderma implementation which has incubation day of 21 (19.08 % ) and dozez of 40 grams. Â  Keywords : biofungisida,Trichoderma, Fusarium oxysporum , tomat